Recommendations for Choosing the Genotyping Method and Best Practices for Quality Control in Crop Genome-Wide Association Studies - Pavan, Stefano; Delvento, Chiara; Ricciardi, Luigi; Lotti, Concetta; Ciani, Elena; D’Agostino, Nunzio (Frontiers in Genetics, 2020)
High-throughput genotyping is boosting genome-wide association studies (GWAS) in crop species, ultimately leading to the identification of single nucleotide polymorphisms (SNPs) and genes associated with economically important traits. Choosing a cost-effective genotyping method for crop GWAS requires careful examination of several aspects, namely the purpose and the scale of the study, crop-specific genomic features, and technical and economic matters associated with each genotyping option. Once genotypic data have been obtained, quality control (QC) procedures must be applied to avoid bias and false signals in genotype-phenotype association tests. QC for human GWAS has been extensively reviewed, however QC for crop GWAS may require different actions, depending on the mating system and breeding activities. Here we review most popular genotyping methods based on next generation sequencing (NGS) and array hybridization, and provide observations that should guide the investigator in the choice of the genotyping method for crop GWAS. We define best practises to perform QC, including actions that are specific for crop species. Finally, we provide an overview of bioinformatics tools that can be used to accomplish all needed tasks. Overall, this work aims to provide guidelines to harmonize those procedures leading to SNP datasets ready for crop GWAS.